Milo imagines the world - e uthor; Robinson, Christian (New York : G.P. Putnam's Sons, 2021)
While Milo and his sister travel to a detention center to visit their incarcerated mother, he observes strangers on the subway and draws what he imagines their lives to be.
School Library Journal, January 2021
Pub Weekly, January 2021
Kirkus Starred, December 2020
4.4
K-3
Keywords: Drawing -- Juvenile fiction; Imagination -- Juvenile fiction; Prisoners' families -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Subways -- Juvenile fiction; Drawing -- Fiction; Imagination -- Fiction; Prisoners' families -- Fiction; Brothers and sisters -- Fiction; Subways -- Fiction